Sensory deprivation without competition yields modest alterations of short-term synaptic dynamics - Finnerty, Gerald T. (The National Academy of Sciences, 2000)
Cortical maps express experience-dependent plasticity. However, the underlying cellular mechanisms remain unclear. We have recently shown that sensory deprivation results in large changes of the short-term dynamics of excitatory synapses at the junction of deprived and spared somatosensory (barrel) cortex, which may contribute to map reorganization. A key issue is whether the alterations in short-term synaptic dynamics are driven by a loss of sensory input or by competition between deprived and spared inputs. Here, we report that short-term dynamics of horizontal pathways in the middle of uniformly deprived cortex change only modestly. Vertical intracortical pathways were unaffected by deprivation. Our results suggest that uniform loss of sensory activity has a limited effect on short-term synaptic dynamics. We concluded that competition between sensory inputs is necessary to produce large-scale changes in synaptic dynamics after sensory deprivation.